2020
DOI: 10.26508/lsa.202000893
|View full text |Cite
|
Sign up to set email alerts
|

Human G-MDSCs are neutrophils at distinct maturation stages promoting tumor growth in breast cancer

Abstract: Myeloid-derived suppressor cells (MDSCs) are known to contribute to immune evasion in cancer. However, the function of the human granulocytic (G)-MDSC subset during tumor progression is largely unknown, and there are no established markers for their identification in human tumor specimens. Using gene expression profiling, mass cytometry, and tumor microarrays, we here demonstrate that human G-MDSCs occur as neutrophils at distinct maturation stages, with a disease-specific profile. G-MDSCs derived from patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 60 publications
(118 reference statements)
0
11
0
Order By: Relevance
“…Neutrophils among TANs with proven immunosuppressive function have been extensively studied and have been named granulocytic myeloid-derived suppressor cells (G-MDSCs) or polymorphonuclear myeloid-derived suppressive cells. G-MDSCs appear as neutrophils at different stages of maturation [ 168 ]. G-MDSCs flexibly adapt to the cancer microenvironment.…”
Section: Neutrophil Plasticity and The Cancer Microenvironmentmentioning
confidence: 99%
“…Neutrophils among TANs with proven immunosuppressive function have been extensively studied and have been named granulocytic myeloid-derived suppressor cells (G-MDSCs) or polymorphonuclear myeloid-derived suppressive cells. G-MDSCs appear as neutrophils at different stages of maturation [ 168 ]. G-MDSCs flexibly adapt to the cancer microenvironment.…”
Section: Neutrophil Plasticity and The Cancer Microenvironmentmentioning
confidence: 99%
“…A single-cell transcriptomic analysis of the myeloid compartment in the splenocytes from two tumor-bearing mice (PyMT tumor model) and 2 tumor-free control animals has suggested that PMN-MDSCs differ from their normal myeloid counterparts and may originate from neutrophil progenitor cells undergoing an aberrant differentiation path ( 82 ). Data from another recent study have suggested that peripheral PMN-MDSCs from patients with metastatic breast cancer are more closely related to healthy donors’ neutrophils than to MDSCs induced in another pathological condition (Gram-positive sepsis) ( 85 ). Further mass-cytometry analysis revealed that unique subpopulations of these granulocytic cells were specifically present in cancer patients, with a majority of low density mature activated neutrophils and a minority of immature neutrophils lacking maturation markers (CD10, CD13, CD45) at different maturation stages.…”
Section: Immunosuppressive Myeloid Cells Of the Granulocytic Lineage:...mentioning
confidence: 99%
“…CXCR2 inhibition prevented neutrophil accumulation in the pancreatic tumors and led to a T cell-dependent suppression of tumor growth [ 94 ]. Mehmeti-Ajradini et al [ 95 ] observed that G-MDSCs isolated from metastatic breast cancer cell patients reduced endothelial expression of CX3CL1 (fractalkine) and prevented infiltration of myeloid immune cells into the tumor.…”
Section: Evidence For Neutrophil Involvement In Cancermentioning
confidence: 99%
“…The G-MDSCs share many traits with immature LDNs that have been released from the bone-marrow before reaching full maturity [ 161 ]. However, not all LDNs are G-MDSCs [ 158 ], and G-MDSCs found in cancer may display heterogeneous morphology, including blast-like myelocytes, banded neutrophils as well as mature neutrophils [ 95 ]. G-MDSCs also share many pro-tumor features of tumor-associated neutrophils (TANs) [ 40 ].…”
Section: Neutrophil Heterogeneity and Subpopulations In Cancermentioning
confidence: 99%